Peningkatan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Keaktifan dan Prestasi Belajar - Arindrawati, Wiwik (Jurnal Ilmiah IKIP Mataram, 2023)
The purpose of this research is to increase the student’s activeness and learning achievement by applying the jigsaw type cooperative learning model to the Energy Source material. The research design used was classroom action research (CAR) with each cycle consisting of four stages, namely planning, action, observation, and reflection. The research subjects were fourth grade students of Sentong State Elementary School, Krejengan District, Probolinggo Regency in the odd semester of the 2021/2022 academic year. The results showed an increase in the mastery of student learning outcomes from cycle 1 to cycle 2 by 19%. The increase in the average class from cycle 1 to cycle 2 is 9. In cycle 1 the percentage of mastery learning is 36% and the class average is 58.64 with 40% student activity. While the second cycle of learning completeness is 93% and the average class is 77.1 with student activity reaching 95%. This shows that when learning science activities with the application of the jigsaw type cooperative model there is a positive improvement in science learning outcomes.